Biological action mechanisms of fucoxanthin extracted from algae for application in food and cosmetic industries - Lourenço-Lopes, Catarina (2018)
Background: Fucoxanthin is a pigment present in diverse marine organisms such as micro and macro-algae. The most relevant source of fucoxanthin has been described to be the group of the brown macroalgae, also known as Phaeophyceae. The presence of the fucoxanthin, a xanthophyll, found as an accessory pigment in the chloroplasts of the brown algae is responsible for providing them their characteristic color. The market size of this carotenoid, expected to reach US$ 120 million by 2022, reflects its industrial importance, especially remarkable as a food or cosmetic ingredient. Scope and approach: Therefore, it is critical to recognize the main sources of fucoxanthin as well as the most efficient extraction and purification methods that allow obtaining the best production ratio for such a valuable molecule. Throughout this review very different preventive properties of the fucoxanthin have been included, such as antioxidant, anticancer, antiangiogenic, anti-inflammatory, cytoprotective, antiobesity, neuroprotective and its skin protective effects. The stability, bioavailability and toxicity of the fucoxanthin have also been reviewed through diverse biological, in vitro and in vivo assays. Key findings and conclusions: Thus, the main aim of this work is to provide a wide and global vision of the fucoxanthin in terms of productive species, efficient recovery techniques and multiple industrial applications.